DIVERSITY AND INCLUSION IN FINTECHS: AN OVERVIEW OF D&I PRACTICES IN BRAZILIAN FINTECHS - Teixeira, Thalya Teles; Duarte, Leandro Batista; Santos, Ana Lúcia Carvalho; Belmiro, Maria Orlandia de Melo; Caires e Caires, Fernanda Oliveira (Seven Editora, 2026)
The term diversity refers to the consideration and practices of inclusion, particularly in workplaces, of underrepresented groups such as women, people with disabilities (PwDs), black persons, among others. In Brazil, a recent study by the Brazilian Institute of Geography and Statistics (IBGE, 2023) on workplace diversity revealed persistent inequalities in gender, race, and inclusion. Fintechs - Financial Startups - are regarded as disruptive enterprises that drive technological and managerial innovation. Consequently, they tend to adopt a greater number of Diversity & Inclusion (D&I) initiatives. Against this backdrop, this study aims to outline the D&I landscape within Brazilian Fintechs by analyzing their implemented actions. To this end, selected Fintechs with more accessible sustainability reports were examined. The research adopts a bibliographic and documentary methodology. Findings indicate that the analyzed Fintechs often outperform both the general labor market and even other startups in D&I metrics. This aligns with expectations, given that the studied firms are larger and implement numerous ESG (Environmental, Social, and Governance) related initiatives. However, challenges persist for certain groups - such as PwDs, LGBTQIA+ individuals, and professionals aged 50+ - where significant progress is still needed to enhance their representation. Moreover, mere numerical inclusion is insufficient; these companies must develop targeted strategies to dismantle the "glass ceiling" and foster equitable advancement opportunities.